2012
DOI: 10.5228/kstp.2012.21.5.324
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Yield Asymmetry Behavior of Indirect-extruded Mg-Sn-Al-Zn Alloys

Abstract: Mg-(9-x)Sn-xAl-1Zn (x=1, 2, 3 and 4 wt.%) alloys were subjected to indirect extrusion, and the microstructure and mechanical properties of the as-extruded Mg-Sn-Al-Zn (TAZ) alloys were investigated. The TAZ 811 alloy exhibited a finer grain structure than the TAZ 541 alloy due to a larger number of Mg 2 Sn particles, which pinned the grain boundaries and prevented growth of recrystallized grains. The TAZ alloys showed an unusual yield asymmetry behavior. The tensioncompression yield asymmetry increased with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…Furthermore, it has been recently reported that fine precipitates formed during extrusion play a significant role in suppressing grain growth through pinning, thereby resulting in a remarkably refined grain structure [18]. Hence, grain boundary pinning by the dispersed Mg 2 Sn precipitates evident in the micro-beam diffraction pattern will also contribute to the formation of an ultrafine grain structure; the shape and size of these Mg 2 Sn precipitates are consistent with previous results relating to indirectly extruded TAZ811 alloys [5,19]. The 10% CPF extruded alloy exhibits excellent tensile properties with a TYS of 387 MPa, a UTS of 403 MPa, and an EL of 7.9%, which are significantly higher than the 343 MPa TYS, 363 MPa UTS, and 6.4% EL of the non-CPF extruded alloy.…”
Section: Resultssupporting
confidence: 79%
“…Furthermore, it has been recently reported that fine precipitates formed during extrusion play a significant role in suppressing grain growth through pinning, thereby resulting in a remarkably refined grain structure [18]. Hence, grain boundary pinning by the dispersed Mg 2 Sn precipitates evident in the micro-beam diffraction pattern will also contribute to the formation of an ultrafine grain structure; the shape and size of these Mg 2 Sn precipitates are consistent with previous results relating to indirectly extruded TAZ811 alloys [5,19]. The 10% CPF extruded alloy exhibits excellent tensile properties with a TYS of 387 MPa, a UTS of 403 MPa, and an EL of 7.9%, which are significantly higher than the 343 MPa TYS, 363 MPa UTS, and 6.4% EL of the non-CPF extruded alloy.…”
Section: Resultssupporting
confidence: 79%